Stauromedusae of the genus Manania (= Thaumatoscyphus) (Cnidaria, Scyphozoa) in the northeast Pacific, including descriptions of new species Manania gwilliami and Manania handi - Larson, R. J.; Fautin, D. G. (Canadian Journal of Zoology, 1989)
Manania gwilliami n.sp. and Manania handi n.sp., stauromedusae belonging to the family Depastridae, are described from the west coast of North America. They are differentiated from the one species of the genus previously known from that area, M. distincta (Kishinouye, 1910) by shape, color, habitat, and geographic range. Specimens of M. gwilliami are generally red and those of M. handi are green; both lack the dark brown herringbone patterning of M. distincta medusae. Manania gwilliami is widely distributed from Mexico to Canada in exposed shallow-water coastal habitats, whereas M. handi has been found only off the San Juan Islands and Vancouver Island in protected shallow water. The occurrence of M. distincta in the northeast Pacific has been sporadic. The name Manania is a senior synonym of Thaumatoscyphus.